Remittance Volatility and Health Sector Performance: Evidence From Nigeria - Emmanuel Busuyi Oguntomi; Sunday Osahon Igbinedion (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This study seeks to investigate the nexus between remittance volatility and life expectancy at birth within the Nigeria context. This study utilizes the ex-post facto research approach by seeking to ascertain the relationship between volatility in remittance and health sector performance within the framework of the Fully Modified Ordinary Squares (FMOLS) and Error Correction Model (ECM) for the period 1981 to 2018. Secondary data sourced from the Central Bank of Nigeria (CBN) Statistical Bulletin and World Development Indicators (WDI) were utilized. Findings suggest that while remittance volatility has statistically significant negative impact on life expectancy in the long-run, it was however positive but insignificant in the short-run. Other factors such as income, education status and public health expenditure were also found to be major determinants of life expectancy in Nigeria. Given that remittances are largely susceptible to external shocks, and are beyond the control of policy makers in the recipient countries, relevant measures should be put in place in the home front to significantly cushion the negative impact of such fluctuations on life expectancy in the long-run.